Unveiling Rosmarinic Acid: Understanding Its Broad Spectrum of Bioactivities - Leong, Ka Fai; Chen, Zihan; Coghi, Paolo (Planta Medica, 2025)
Rosmarinic acid (RA) is a polyphenolic compound with various biological activities found in numerous traditional medicinal plants. Moreover, RA is already used as a food additive, demonstrating its safety. Current research has identified RA as having diverse effects, including sedative, hypnotic, antiepileptic, anti-Parkinson, neuroprotective, antidepressant, anti-inflammatory, antioxidant, cognitive-enhancing, metabolic-regulating, antimicrobial, and antitumor properties. Nevertheless, the mechanisms underlying these effects remain incompletely understood. This review attempts to define the mechanisms of its bioactivity by correlating RAʼs effect on different biomolecules. We performed an extensive search across major databases, using the core keyword “Rosmarinic acid” with relevant keywords to construct search queries. Our findings suggest that some mechanisms are shared among RAʼs various activities. For example, the chemical structure of RA itself makes it an antioxidant, and the antioxidant effect enables it to reduce inflammation caused by active substances such as ROS and free radicals. Its antioxidant and anti-inflammatory effects can relieve pain, provide neuroprotection, reduce chronic adipose inflammation, and improve insulin sensitivity. RA can also inhibit the aggregation of harmful proteins and promote their degradation, which plays a key role in neuroprotection and cognitive improvement. RAʼs modulation of neurotransmitters exerts both antidepressant effects and benefits on cognitive impairment. The regulation of key pathways by RA–such as ERK1/2, MAPK, STAT3, PI3K, Akt, NF-κB, and Nrf2–is central to its antioxidant, anti-inflammatory, lipid- and glucose-regulating, and antitumor effects.
Keywords: Rosmarinic acid; Melissa officinalis; Lamiaceae; Pharmacology; Bioactivity